An analysis of the negative impact of the culture of achieving `simple ippons` on international sporting performance: The case of Japanese elite judo - Wu, D.-Y., Nakamura, H.; Iteya, M.; Kimura, M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Problem. In this study, the influence of Japanese judo culture on international sporting performance was explored by conducting a longitudinal analysis of Japanese elite judo development from 1996 to 2012. Sport management research has revealed that although the influence of elite sporting culture on international performance can be not only positive but also negative, it is hard to find an empirical examination thereof for its negative impact. Method. We, therefore, developed a theoretical framework in accordance with the research that has explored the similarity and convergence of elite sport policies. Using documentary analysis and supplementary information from interviews, we examined how the national Japanese elite judo team enacted on their interpretation of the culture of achieving simple ippons and how the culture in teams thwarted superior sporting performances. Results and Conclusions. The results revealed that elite sporting culture does not always enhance sporting performances as well as the processes and conditions involved in national teams failing to control the influence of the culture.